Analysis of Legal And Ethical Regulation of Testamentary Matters in Nigeria: Has it Halted Inheritance Disputes? - OLUJOBI, Olusola Joshua; OYEWUNMI, Olabode Adeleke; IYOHA, Odianonsen Francis (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
Generally speaking, the practice of documenting testaments is not prevalent amongst Nigerians, particularly such testaments that reinforce the inevitability of one’s death. Nigeria’s legal framework indeed provides ample latitude and freedom for the testator to allocate his property. Instructively, the testators’ established intentions and the import of prevailing customary laws must be duly construed. It highlights the tension between customary law and testamentary dispositions. However, the evident conflict in terms of interpretation of the applicable laws and established practices may portend diverse and unpredictable outcomes for the matrix of stakeholders. The paper constitutes a robust legal critique, while utilizing descriptive approach with relevant secondary sources such as academic journals, statutes and textbooks. It highlights the importance of writing one’s will. It explores library-based approach to explore relevant judicial and statutory authorities, and legal opinion on testamentary matters. It is opined that; the essence of the ‘Wills Act’ is to secure a valid and reasonable interpretation of the testator’s dictates. This paper recommends the need for due compliance with the testators’ wishes as well as the importance of fostering a culture of documenting one’s testamentary intentions in Nigeria to prevent disputes over inheritance after the testator’s demise